Analysis of Mandailing Tribe Students Who Experience Inner Child Dynamics Towards Social Life - Siagian, Dina Mardiana; Nuriza Dora (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the dynamics of the inner child experienced by Mandailing students and its impact on their social life in the State Islamic University of North Sumatra. The background of this study is based on the importance of understanding unresolved childhood wounds (inner child), especially in the context of Mandailing culture which is known to have a strong, hierarchical, and thick parenting pattern with traditional values. The approach used in this study is qualitative with a case study method. Data were obtained through in-depth interviews, observations, and documentation of several Mandailing student informants who were selected purposively. The results of the study indicate that childhood experiences related to emotional stress, authoritarian parenting patterns, and social expectations from families and traditional communities have a significant impact on students' social relationships on campus. Some of them have difficulty expressing emotions, building healthy interpersonal relationships, and a tendency to suppress inner conflicts. However, there are also forms of resilience that emerge, such as the drive to be independent and academic success as a form of compensation. This study concludes that the dynamics of the inner child in the context of Mandailing culture have a complex influence on the social life of students, which requires a psychosocial approach that is sensitive to cultural values ​​and personal experiences